Pencegahan Stunting Melalui Edukasi MP-ASI Kepada Masyarakat Desa Saringembat dalam Bentuk Inovasi Menu Makanan Menggunakan Bahan Lokal dan Praktik Pembuatan MP-ASI Kepada Ibu Balita - Taufikurrahman Taufikurrahman; Citra Nia Ramadhani; Fatika Permatasari; Verend Sirlya; Moch. Bahrul Alamsyah (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Stunting is a condition of impaired child growth due to chronic malnutrition during the 1,000 First Days of Life (HPK), affecting physical, cognitive, and social development. In Indonesia, stunting remains a major challenge, particularly among toddlers. Providing appropriate Complementary Feeding (MP-ASI) for children aged 6-24 months is key to prevention. This article discusses an educational program for stunting prevention through the development of MP-ASI menus in Saringembat Village. The program aims to increase community awareness of the importance of balanced nutrition through three main stages: determining MP-ASI menus, preparing educational materials, and conducting socialization and MP-ASI-making practices. The menus are divided into three age groups (6-8 months, 9-12 months, and over 12 months) using local ingredients such as catfish, spinach, and potatoes.The results show increased community understanding, the effectiveness of using local ingredients, and the success of hands-on practice. A final evaluation quiz indicated that most participants understood the concept of MP-ASI and stunting prevention. This program is expected to continue to help reduce stunting rates and create a healthier generation.